A Technology-Driven Approach in Financial Management - P. Viswanath, (AG Volumes, 2024)
The planning, procurement, deployment, and control of a company's financial resources are all included in the management function known as financial management. Financial management is often mistaken with accounting since it is commonly nested within the accounts and finance function in many organizations, and vice versa. In this article it is tried to present different approaches to financial management and focused on the reviewing various literature’s study on technology-driven approach in financial management. It concluded that the digital era has revolutionized financial management by enhancing efficiency through virtual payments, automation, and AI-driven decision- making. Machine learning strengthens risk management and regulatory oversight, optimizing financial resilience. However, evolving business models and skill requirements necessitate adaptive management. While digitalization and datafication offer immense economic benefits, they also introduce financial risks that require mitigation. The companies which adopts and practice the ever-changing technologies and embrace these transformations will dictate the future of business and the rest eventually exit from business.